2012
DOI: 10.4161/cc.22386
|View full text |Cite
|
Sign up to set email alerts
|

B-Myb promotes S-phase independently of its sequence-specific DNA binding activity and interacts with polymerase delta-interacting protein 1 (Pdip1)

Abstract: B-Myb is a highly conserved member of the Myb transcription factor family, which plays an essential role in cell cycle progression by regulating the transcription of genes at the G 2/M-phase boundary. The role of B-Myb in other parts of the cell cycle is less well-understood. By employing siRNA-mediated silencing of B-Myb expression, we found that B-Myb is required for efficient entry into S-phase. Surprisingly, a B-Myb mutant that lacks sequence-specific DNA-binding activity and is unable to activate transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 57 publications
3
25
0
Order By: Relevance
“…In addition to the classical role of MYBL2 as a transcription factor at the G2/M-transition, the results indicated that MYBL2 might also be involved in processes related to DNA synthesis or repair in GBC, consistent with previous reports [38-40]. In the present study, we examined the effect of silencing of MYBL2 expression on DNA synthesis in GBC cell lines, and the results suggested that DNA synthesis and/or entry into the S-phase was compromised in cells after MYBL2 knockdown.…”
Section: Discussionsupporting
confidence: 81%
“…In addition to the classical role of MYBL2 as a transcription factor at the G2/M-transition, the results indicated that MYBL2 might also be involved in processes related to DNA synthesis or repair in GBC, consistent with previous reports [38-40]. In the present study, we examined the effect of silencing of MYBL2 expression on DNA synthesis in GBC cell lines, and the results suggested that DNA synthesis and/or entry into the S-phase was compromised in cells after MYBL2 knockdown.…”
Section: Discussionsupporting
confidence: 81%
“…Similar to what has previously been reported, we identified an enrichment of cell cycle genes directly regulated by Myb, with the majority being G2/M but also several S phase genes (consistent with studies on B-Myb, supporting its role in S phase; Lam et al, 1992;Werwein et al, 2012). Notably, a recent study reported that Cyclin A (the cyclin that regulates aspects of both S phase and G2/M) directly binds to Myb and is required for expression of many of its targets (Rotelli et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…55 Interestingly, B-Myb has also been reported to be required for S-phase entry and to interact with Poldip1, a Pol δ-interacting protein. 56 hOGG1 is a DNA glycosylase involved in the initial step of base excision repair of oxidized purines, and APE1 catalyzes the next step. Both are recruited to nuclear speckles in response to UVA but not by UVC.…”
Section: Discussionmentioning
confidence: 99%